Pengembangan Instrumen Tes untuk Meningkatkan Kemampuan Multirepresentasional Peserta Didik - Fajri Alifah; Edi Istiyono (Postgraduate, University of Mataram, 2023)
The aim of this research is to determine the feasibility of a physics test instrument to measure high school students' multiple representation abilities in rectilinear motion material and to determine the characteristics of respondents' multirepresentation abilities in rectilinear motion material. The development of this instrument was carried out using a modified development method of the Wilson, Oriondo, and Antonio. Students' multiple representation abilities were analyzed with the help of Quest which was then analyzed further using descriptive statistics. The results of this research are in the form of a test instrument to measure high school students' multi-representation abilities in rectilinear motion material consisting of 20 two-tier multiple choice questions. The items in the questions are valid, fit the PCM 1 PL model, have very good reliability with a score of 0.84, and have a good level of difficulty. The results of item analysis and analysis of students' abilities show that the instrument developed is effective in measuring high school students' multi-representational abilities in rectilinear motion material.